2022
DOI: 10.1097/md.0000000000029595
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with long-term smoking relapse in those who succeeded in smoking cessation using regional smoking cessation programs

Abstract: It is known that approximately 10% of successful quitters relapse annually. This study aimed to investigate the factors related to long-term smoking relapse in individuals who succeeded in maintaining smoking cessation for 6 months after attending a regional smoking cessation program.This study enrolled 943 individuals registered for the regional smoking cessation program at the Busan Smoking Cessation Center in 2018-2019 who maintained smoking cessation for 6 months. A survey was conducted using a smartphone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…During a quit attempt women were more disadvantageous than men in terms of maintaining abstinence (20). In contrast, Lee et al (21) found no difference between non-relapsed and relapsed individuals in terms of gender. In the present study, male/female ratio was comparable between quitters and non-quitters.…”
Section: Discussionmentioning
confidence: 94%
“…During a quit attempt women were more disadvantageous than men in terms of maintaining abstinence (20). In contrast, Lee et al (21) found no difference between non-relapsed and relapsed individuals in terms of gender. In the present study, male/female ratio was comparable between quitters and non-quitters.…”
Section: Discussionmentioning
confidence: 94%
“…According to previous studies, smoking relieves stress, and high levels of emotional stress are associated with long-term smoking relapse in 305 participants. 9 The group with major depressive disorder (MDD) had a lower continuous abstinence rate over 6 months than the non-MDD group of 1245 smokers using the Korea NHIS smoking cessation program. 22 In a Chinese study, depression was associated with a high risk of relapse for quitters aged < 60 years in 1019 smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco craving questionnaire (≤ 202, ≥ 203 points). 16 Self-efficacy scores for smoking cessation were divided into tertiles (low [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], middle [25][26][27][28][29][30], and high [31-45]). 17 The drug regimens included NRT, including nicotine patches, lozenges, gum, and prescription drugs (varenicline or bupropion).…”
Section: Risk Factors' Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…However only less than 10% of those who attempt could remain abstinent for at least 6 months 5 , 6 . In addition, approximately 10% of quitters relapse annually 7 .…”
Section: Introductionmentioning
confidence: 99%